Early Childhood Mindset Stimulation for Understanding Pancasila Through Affective Education - Banamtuan, Maglon F; Natonis, Harun Y (Program Studi Magister Pendidikan Anak Usia Dini, 2019)
This study aims to find out how to stimulate Early Childhood Mindset in Theodeosius kindergarten through affective education. This research is qualitative research. Data analysis is done by reducing data, presenting data, and drawing conclusions. The research findings show that students are very enthusiastic about following the activities of the teacher with pleasure, happiness and not feeling burdened from the beginning of the activity to the end, students can take part in the activities of the teacher well. The efforts made by TK Theodosius educators are good, so that it can be said that the teacher's efforts to train children's independence are maximized. The students have begun to instill Pancasila values in their daily lives, namely Godhead, Humanity, the Value of Unity, People's Value, and Social Justice. Keywords: Affective Education, Early Childhood Mindset Stimulation, Understanding Pancasila. References Abramson, L., Daniel, E., & Knafo-noam, A. (2018). Journal of Experimental Child The role of personal values in children ’ s costly sharing and non-costly giving. Journal of Experimental Child Psychology, 165, 117–134. https://doi.org/10.1016/j.jecp.2017.03.007 Aydoğan, C., Farran, D. C., & Sağsöz, G. (2015). The relationship between kindergarten classroom environment and children’s engagement. European Early Childhood Education Research Journal, 23(5), 604–618. https://doi.org/10.1080/1350293X.2015.1104036 Bowo, T. A., & Budiati. (2017). Model Pembelajaran Bahasa Inggris Interaktif Menggunakan Flascard Berbasis Pancasila Sebagai Upaya Pembentukan Karakter Bangsa. Media Penelitian Pendidikan, 11(2), 59–74. Cartledge, G., & Milburn, J. F. (1980). Teaching social skills to children. Pergamon Press. Chou, S. Y., & Pearson, J. M. (2012). Organizational citizenship behaviour in IT professionals: An expectancy theory approach. Management Research Review, 35(12), 1170–1186. https://doi.org/10.1108/01409171211281282 Decety, J., Meidenbauer, K. L., & Cowell, J. M. (2018). The development of cognitive empathy and concern in preschool children: A behavioral neuroscience investigation. Developmental Science, 21(3), 1–12. https://doi.org/10.1111/desc.12570 Dodge, D. T. (2004). Early Childhood Curriculum Models Why What and How Programs Use them. Exchange Organizational Behavior Teaching Journal, (February), 71–75. Domitrovich, C. E., Durlak, J. A., Staley, K. C., & Weissberg, R. P. (2017). Social-Emotional competence: An essential factor for promoting positive adjustment and reducing risk in school children. Child Development, 88(2), 408–416. https://doi.org/10.1111/cdev.12739 Dunlap, G., Powell, D., & Org, W. C. (2009). Promoting Social Behavior of Young Children in Group Settings: A Summary of Research. Technical Assistance Center on Social Emotional Intervention for Young Children, (August). Retrieved from www.challengingbehavior.org Emilson, A., & Johansson, E. (2013). Values in Nordic Early Childhood Education: Democracy and the Child’s Perspective. Choice Reviews Online, 30(11), 30-6297-30–6297. https://doi.org/10.5860/choice.30-6297 Ertürk, A. (2007). Increasing organizational citizenship behaviors of Turkish academicians. Journal of Managerial Psychology, 22(3), 257–270. https://doi.org/10.1108/02683940710733089 Esnard, C., & Jouffre, S. (2008). Organizational citizenship behavior: Social valorization among pupils and the effect on teachers’ judgments. European Journal of Psychology of Education, 23(3), 255–274. https://doi.org/10.1007/BF03172999 Grajczonek, J., & Truasheim, M. (2017). Implementing Godly Play in educational settings: a cautionary tale. British Journal of Religious Education, 39(2), 172–186. https://doi.org/10.1080/01416200.2015.1110112 Hamid. (2015). Semiotika Kewarganegaraan. Bandung: Rizqi Press. Hildebrandt, C., & Zan, B. (2015). Pendekatan Konstruktivis pada Pendidikan Moral Anak Usia Dini. In Handbook Pendidikan Moral dan Karakter (pp. 511–536). Bandung: Nusa Media. Hurlock, E. B. (1999). Perkembangan Anak Jilid I. (Erlangga, Ed.). jakarta. Hurlock, E. B. (2010). Perkembangan Anak (6th ed.). Jakarta: Erlangga. Mahanani, P., Purnama Putra, A., & Kristianingsih, K. (2018). Analysis of the Influence of Understanding the Pancasila Values of Teachers on Learning in Elementary School, 244(Ecpe), 168–172. https://doi.org/10.2991/ecpe-18.2018.37 Mayfield, C. O., & Taber, T. D. (2010). A prosocial self-concept approach to understanding organizational citizenship behavior. Journal of Managerial Psychology, 25(7), 741–763. https://doi.org/10.1108/02683941011075283 Nicholson, J., Kuhl, K., Maniates, H., Lin, B., Bonetti, S., Nicholson, J., … Bonetti, S. (2018). A review of the literature on leadership in early childhood : examining epistemological foundations and considerations of social justice, 4430. https://doi.org/10.1080/03004430.2018.1455036 Organ, D. W. (1988). Organizational citizenship behavior: The good soldier syndrome. Lexington: Lexington Books. Podsakoff, P. M., MacKenzie, S. B., Moorman, R. H., & Fetter, R. (2015). Transformational Leader Behaviors and Their Effects on Trust , Satisfaction , and Organizational Citizenship Behaviors. JAI Press Inc., (August), 107–142. https://doi.org/10.1016/1048-9843(90)90009-7 Podsakoff, P. M., MacKenzie, S. B., Paine, J. B., & Bachrach, D. G. (2000). Organizational Citizenship Behaviors: A Critical Review of the Theoretical and Empirical Literature and Suggestions for Future Research. Journal of Management, 25(3), 513–563. https://doi.org/10.1016/0009-2614(78)85552-3 Robson, J. V. K. (2019). How do practitioners in early years provision promote Fundamental British Values ? How do practitioners in early years provision promote, 9760. https://doi.org/10.1080/09669760.2018.1507904 Ronald Silalahi, U. yuwono. (2016). Research in social sciences and technology. Research in Social Sciences and Technology, 2(3), 58–57. Retrieved from http://www.ressat.org/index.php/ressat/article/view/329 Samuelsson, I. P., & Hagglund, S. (2009). Early Childhood Education and Learning for Sustainable Development and Citizenship. International Journal, 41(2), 49–63. Sanjaya, W. (2013). Penelitian Pendidikan (Jenis, Metode, dan Prosedur),. Jakarta: Kencana Prenada Media Group. Stephens, M., & Ormandy, P. (2018). Extending conceptual understanding: How interprofessional education influences affective domain development. Journal of Interprofessional Care, 32(3), 348–357. https://doi.org/10.1080/13561820.2018.1425291 LK - Stevenson, B. (2017). Children’s independence: a conceptual argument for connecting the conduct of everyday life and learning in Finland. Children’s Geographies, 15(4), 439–451. https://doi.org/10.1080/14733285.2016.1271942 UNESCO. (2014). Preparing learners for the challenges of the 21st century. France: UNESCO. Retrieved from http://www.unesco.org/new/en/global-citizenship-education UNESCO. (2015). Global citizenship education: topics and learning objectives.